2018
DOI: 10.1007/s13744-018-0626-3
|View full text |Cite
|
Sign up to set email alerts
|

Lethal and Sublethal Toxicity of Insecticides to the Lacewing Ceraeochrysa Cubana

Abstract: The lethal and sublethal effects of 11 insecticides on the predator Ceraeochrysa cubana (Hagen) were assessed under laboratory conditions. First-instar larvae and adults ≤ 48 h old were sprayed with the highest insecticides doses allowed to control Diaphorina citri Kuwayama in the citrus crop. The survival and duration rates of the different development stages, sex ratio, pre-oviposition period, fecundity, and fertility of the insects were evaluated. In the larval bioassay, chlorpyrifos and malathion had letha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
4
6
0
1
Order By: Relevance
“…Acetamiprid and dinotefuran had no significant negative effects on adult longevity, fecundity, oviposition days, preadult survival rate, r, λ, R 0 , T, and GRR of the C. pallens population. Our results are consistent with the results of other studies: imidacloprid had no negative effects on the fertility, R 0 , r, and T of Ceraeochrysa cubana [39]; imidacloprid and thiamethoxam had no significant effects on the population parameters (R 0 , r, and T) of Iphiseiodes zuluagai [40]; and thiamethoxam had no significant effect on adult longevity and fecundity of H. variegata [38]. However, other studies have reported that neonicotinoid insecticides induce great damage to beneficial arthropods.…”
Section: Discussionsupporting
confidence: 93%
“…Acetamiprid and dinotefuran had no significant negative effects on adult longevity, fecundity, oviposition days, preadult survival rate, r, λ, R 0 , T, and GRR of the C. pallens population. Our results are consistent with the results of other studies: imidacloprid had no negative effects on the fertility, R 0 , r, and T of Ceraeochrysa cubana [39]; imidacloprid and thiamethoxam had no significant effects on the population parameters (R 0 , r, and T) of Iphiseiodes zuluagai [40]; and thiamethoxam had no significant effect on adult longevity and fecundity of H. variegata [38]. However, other studies have reported that neonicotinoid insecticides induce great damage to beneficial arthropods.…”
Section: Discussionsupporting
confidence: 93%
“…Results were agreed with those reported by , who reported the adverse impact on this predator. Also, our results matched those reported by Rugno et al (2019) when they studied the impact of 11 insecticides on the predator Chrysoperla cubana from first instar larvae to adults; he reported that showing the negative effects of these tested insecticides.…”
Section: Chrysoperla Carnea Larval and Adult Treatmentssupporting
confidence: 90%
“…The sub-lethal and lethal effects of 11 insecticides were assessed against Ceraeochrysa cubana. The malathion and chlorpyrifos were observed with lethal effects and lambda cyhalothrin+ chlorantraniliprole, azadirachtin, thiamethoxam+lambda-cyhalothrin, thiamethoxam with sub-lethal effects (Rungo et al, 2019). ANOVA was found with a significant difference (DF= 5; F= 225.68; P= 0.03) on post-spray days.…”
Section: Application Of Helmet Insecticide On Lemon Leaves Against P ...mentioning
confidence: 85%